How Dependency on Social Media Can Help Improve Student Achievement in Online Learning - A.R, Widhi; Triyonowati, Triyonowati; Arsyad, M. (Budapest International Research and Critics University, 2021)
In this pandemic era, social media plays a significant role for students, both as a means of communication and seeking entertainment. The learning system uses e-learning and WhatsApp groups as a medium of communication between lecturers and students. The student participation is monitored through how the students are active in discussions on WhatsApp groups and timeliness in completing assignments. This condition makes students spend a lot of time using social media particularly WhatsApp in their daily lives and using Instagram, YouTube, and TikTok as entertainment media. This study aimed to see how gender, age, and personality influence student achievement during this pandemic with dependency on social media as a mediating variable. In this study, the dependent variable was student achievement and the independent variable was personality and demographic factors. Knowing the relationship between these variables was done by using the PLS analysis tool. Based on statistical tests, it was known that addiction to social media could not mediate the relationship between demographic factors and student achievement. Personality could affect achievement indirectly by being mediated by dependency on social media. This condition could occur because in the pandemic all kinds of communications related to academic activities were carried out using WhatsApp group as social media. It means the more students are fully involved in the WhatsApp group, the more knowledge will be gained. Thus, it could help students completing assignments and exams. While the consequence of this was the frequency of time spent on social media was increasing.